Obtaining the gravitational force corresponding to arbitrary spacetimes. The Schwarzschild’s case. - Soldovieri, T.; Muñoz S., A.G. (Revista Mexicana de Física, 2003)
Making use of the classical Binet’s equation a general procedure to obtain the gravitational force corresponding to an arbitrary 4-dimensional spacetime is presented. This method provides, for general relativistic scenarios, classics expressions that may help to visualize certain effects that Newton’s theory can not explain. In particular, the force produced by a gravitational field which source is spherically symmetrical (Schwarzschild’s spacetime) is obtained. Such expression uses a redefinition of the classical reduced mass, in the limit case it can be reduced to Newton’s universal law of gravitation and it produces two different orbital velocities for test particles that asimptotically coincide with the Newtonian one. As far as we know this is a new result.